Formulasi Masker Peel Off Ekstrak Buah Naga Merah (Hylocereus lemairei Hook.) dan Pati Jagung dengan Variasi Konsentrasi Polyvinyl Alcohol (PVA) - Ni Made Dharma Shantini Suena; I Gusti Agung Ayu Kusuma Wardani; Ni Putu Udayana Antari (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2023)
Red dragon fruit is rich in nutrients and minerals as well as phytoalbumin and antioxidant compounds such as phenolic compounds and vitamin C. Corn contains vitamins A, B, and E as antioxidants, as well as Thiamin, which can reduce black spots on acne scars and dry out wounds. Peel-off masks are cosmetic preparations for facial care that can form a thin, transparent layer on the surface of the skin and can be peeled off after drying, so they are practical to use. Polyvinyl alcohol (PVA) is a film-forming polymer and can increase viscosity, which in turn plays a role in producing peel-off masks that have good physical quality. This study aims to formulate peel-off masks of red dragon fruit extract (Hylocereus lemairei Hook.) and corn starch with varying concentrations of PVA (F1:2.5%, F2:8.75%, F3:17.5%) in order to have a high-quality good physique. The evaluation of the physical quality of the red dragon fruit and corn starch peel-off masks was organoleptic, homogeneity, pH, spreadability, adhesion, and drying time. The organoleptic preparations (F1-F3) were brownish-orange in color, with a distinctive rose odor, with increased viscosity from F1 to F3, and remained stable for up to 4 weeks of storage. The homogeneity of preparation (F1-F3) was homogeneous and lasted for 4 weeks of storage. The pH value of the preparation on day 1, F1 and F2, had a pH of 4, and F3 had a pH of 4.5. From the 1st to the 4th week, the pH of preparations F1-F3 was 4.5, according to the physiological pH of the skin, 4-8. The spreadability of F1-F3 preparations was in the 5.5-6.5 cm range, according to 5-7 cm provisions. The adhesive power of the F1-F3 preparations was in the range of 5.29-40.1 seconds, which is recommended for more than 1 second. The drying time of F1-F3 preparations was in the range of 20.58-30.45 minutes, according to the provisions of 15-30 minutes. The three red dragon fruit and corn starch peel-off mask formulas (F1, F2, and F3) meet the requirements for good physical quality according to the criteria set and recommended. Increasing the PVA concentration did not affect the pH value and spreadability of the three formulas but increased the adhesiveness value and drying time.